The Influence Of Service Quality, Trust And Customer Satisfaction On Maxim's Customer Loyalty In Medan City - Harada Rahmi; Kartini Harahap (Journal of Economics and Business (JECOMBI), 2023)
This study aims to determine the effect of service quality, trust and customer satisfaction on consumer loyalty maxim in the city of Medan. The influence of service quality, trust and customer satisfaction will be analyzed partially and simultaneously on Maxim customer loyalty in Medan City. The research method used is associative research with a quantitative approach. The population in this study were Maxim consumers in Medan City, with a sample of 100 respondents. The sampling technique uses non-probability sampling with a purposive sampling technique. Primary data was obtained from questionnaires which were distributed via google form, while secondary data was obtained through library data. Methods of data analysis using instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the research conducted show that the variables of service quality (X1), trust (X2) and customer satisfaction (X3) have a positive and significant effect on customer loyalty. However, the variables of service quality, trust and customer satisfaction have a simultaneous effect on consumer loyalty (Y). The coefficient of determination test shows that there is a close relationship between service quality, customer trust and satisfaction on consumer loyalty with an R value of 83.6%. Through the value of the Adjusted R square it is known that the variables of service quality, trust and customer satisfaction contribute 69% to the consumer loyalty variable while the remaining 31% is influenced by other variables not discussed in this study.